PCR based analysis of single nucleotide polymorphsim in beta-casein A1 and A2 gene of bovine in Bangladesh - Rahman, Olema Taj (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Mathematics 2019.